Ant-Cave-Structured Nanopore-Embedded CoMn2O4 Microspheres with Stable Electrochemical Reaction for Li-Air Battery. Issue 8 (18th May 2020) - Yun, Young Jun; Park, Hyemin; Kim, Jin-Kyu; Unithrattil, Sanjith; Huu, Ha Tran; Kim, Dong Wook; Lee, Sun Sook; Kang, Yongku; Bin Im, Won; Choi, Sungho
Abstract : Herein, nanopore-embedded CoMn2 O4 microspheres were successfully synthesized, and their electrochemical behavior as an anode for lithium-ion batteries (LIBs) and as a catalyst for oxygen-reduction/evolution reactions of lithium-air batteries (LABs) cathodes was investigated. The electrodes composed of specifically designed particles exhibited enhanced capacity retention with stable charge-transfer impedance change during the overall lithium conversion reactions as compared to the electrodes composed of conventional particulate nanoparticles. The LAB cathodes with the as-prepared porous compounds exhibit better reversibility with a ∼10% higher oxygen-evolution reactions efficiency and stable capacity retention than those of the Ketjen black-only electrodes. We believe that these novel performance is achieved due to the rational design of the pore-embedded/interconnected CoMn2 O4 nanoparticles, which mitigate the detrimental volume change during the repetitive Li + ⇄ LiO x reaction and facilitate effective lithium ion (for LIBs) and oxygen diffusion (for LABs) in the porous electrode.